2018
DOI: 10.1007/s11356-018-1889-2
|View full text |Cite
|
Sign up to set email alerts
|

Different relationships between personal exposure and ambient concentration by particle size

Abstract: Ambient particulate matter (PM) concentrations at monitoring stations were often used as an indicator of population exposure to PM in epidemiological studies. The correlation between personal exposure and ambient concentrations of PM varied because of diverse time-activity patterns. The aim of this study was to determine the relationship between personal exposure and ambient concentrations of PM and PM with minimal impact of time-activity pattern on personal exposure. Performance of the MicroPEM, v3.2 was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…However, there are only a few studies that have evaluated the MicroPEM's performance against traditional gravimetric field instruments. Guak and Lee investigated the correlation between personal and ambient concentrations of PM 10 and PM 2.5 by co-locating RTI's MicroPEM (v3.2) against central ambient air monitors for PM 10 and PM 2.5 .The MicroPEM showed a strong linear relationship with the co-located monitors (PM 10 R 2 = 0.89, PM 2.5 R 2 = 0.93), similar to the ECM vs cyclone/pump results we obtained in our study 46. The US Environmental Protection Agency (EPA) also conducted a series of experiments to evaluate the MicroPEM versus the Grimm Model EDM180 PM 2.5 FEM air monitor.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…However, there are only a few studies that have evaluated the MicroPEM's performance against traditional gravimetric field instruments. Guak and Lee investigated the correlation between personal and ambient concentrations of PM 10 and PM 2.5 by co-locating RTI's MicroPEM (v3.2) against central ambient air monitors for PM 10 and PM 2.5 .The MicroPEM showed a strong linear relationship with the co-located monitors (PM 10 R 2 = 0.89, PM 2.5 R 2 = 0.93), similar to the ECM vs cyclone/pump results we obtained in our study 46. The US Environmental Protection Agency (EPA) also conducted a series of experiments to evaluate the MicroPEM versus the Grimm Model EDM180 PM 2.5 FEM air monitor.…”
supporting
confidence: 86%
“…However, past studies have sought to evaluate both laboratory and field performance of just one of these instruments or past versions of the instruments compared to commonly used gravimetric instruments. 18,25,[40][41][42][43][44][45][46][47][48] Although there are no evaluation studies to date that have been conducted on the current version of the ECM, except for a pilot study to compare the ECM to the MicroPEM, 40 in rural India. Correlation between the two instruments was also found to be strong in this preliminary field study (Pearson's r = 0.91, 95% CI 0.84-0.95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each sampler was enclosed in a sturdy cage hung on an IV pole, at a median height of 0.73 m (range 0.5‐1.37 m) above the floor, approximately the height of the child's breathing zone while sleeping, and as close as possible to her/his bed. Prior studies have shown good agreement between MicroPEMs used as gravimetric area samplers and other gravimetric methods at a range of PM 2.5 concentrations 18‐20 . We chose a priori to use the gravimetric rather than the real‐time nephelometer measurements from the MicroPEMs to evaluate HEPA cleaner effectiveness because of evidence of baseline drift in nephelometer data, 21,22 and our concern that this drift would affect the accuracy of our measurements particularly over such a long sample duration (ie, 14 days).…”
Section: Methodsmentioning
confidence: 99%
“…Despite moderate to high correlation between the ambient PM 10 concentrations and personal exposure [14,15], the former can unlikely serve a surrogate to estimate personal exposure to PM 10 in the outdoor workplaces, given that the correlation is different for PM 10 compared to PM 2.5 [14]. Furthermore, no personal exposure to PM 10 in the outdoor workplaces has ever been verified in the cities of Kazakhstan.…”
Section: Introductionmentioning
confidence: 99%